Cortázar’s Word Formation - González García, Luis (2020)
In this paper we analyze the process of word formation in the literary production of Julio Cortázar. After an introductory section focused on his aim of regeneration of the Latin American novel, one of whose pillars is the renewal of the literary lexicon, the rest of the article is devoted to a detailed analysis of the procedures used by Cortázar in the creation of new words. Firstly, we study creations of a jabberwocky nature (jitanjáforas). Afterward, we attend to the use of the regular mechanisms that language offers for this purpose (derivation, composition, blending, palindromes and anagrams, etc.).